The Promoting Role of Digital Inclusive Finance in the Innovation Transformation of Micro and Small Enterprises - Zhang, Xiaoyi (Transactions on Economics, Business and Management Research, 2024)
To comprehend the role of digital inclusive finance (DIF) in facilitating the innovation transformation of Micro and Small Enterprises (MSEs), this study endeavors to establish a theoretical framework incorporating the Long Tail Theory, Financial Development Theory, and Information Asymmetry Theory. Employing a fixed-effects model, the study delves into the impact of DIF on the innovation transformation of MSEs. The findings suggest that DIF significantly mitigates the financing constraints faced by MSEs, thereby fostering their innovation transformation. This study bears both theoretical and practical significance in enhancing the understanding of the mechanism through which DIF promotes the innovation development of MSEs, while also providing a foundational reference for pertinent policy formulation.